Effect of Bariatric Surgery-Induced Weight Loss on SR-BI-, ABCG1-, and ABCA1-Mediated Cellular Cholesterol Efflux in Obese Women - Aron-Wisnewsky, Judith; Julia, Zélie; Poitou, Christine; Bouillot, Jean-Luc; Basdevant, Arnaud; Chapman, M. John; Clement, Karine; Guerin, Maryse (The journal of clinical endocrinology and metabolism, 2011)
Aim:We tested the hypothesis that quantitative changes in high-density lipoprotein (HDL) particles weight loss induced by Roux-en-Y bypass (RYGBP) in morbidly obese subjects might be associated with improved functionality of these particles in the reverse cholesterol transport pathway.Methods and Results:Thirty-four morbidly obese women were recruited and followed up before and 6 months after RYGBP. After surgery, along with a major weight loss (−20%; P < 0.0001), we observed a significant increase in HDL mass concentration (+14%; P < 0.04), reflecting a specific increase in large HDL2 subfraction levels (+42%; P < 0.01), whereas those of HDL3 remained unchanged. Cholesterol ester transfer protein activity decreased significantly (−15%; P < 0.0001). Efflux capacity of total plasma increased significantly via both scavenger receptor class B type I (SR-BI) (+58%; P < 0.0001) and ATP binding cassette G1 (ABCG1) (+26%; P < 0.0001) pathways. Such enhanced capacity resulted from increased capacity of HDL2 particles to mediate cholesterol efflux through the SR-BI pathway (+56%, P < 0.001) and from the increase plasma level of cholesteryl ester-rich HDL2 particles for the ABCG1 pathway.Conclusion:RYGBP-induced weight loss results in improvement in atherogenic lipid profile including a shift toward a more cardioprotective HDL subfraction profile. In addition, our in vitro studies demonstrated an increased in plasma efflux capacity via both SR-BI and ABCG1 after surgery.